PRINCIPLES OF ORGANIZATION OF ARTISTIC TIME IN THE NOVELS OF V. AKSENOV - Gulmatova Ugilshod Gulmatovna (European International Journal of Multidisciplinary Research and Management Studies, 2022)
The work of Vasily Aksenov has attracted the attention of American readers and literary critics for many years. His works are quickly translated into English, and many are included in the list of required literature for students of Slavic studies in American colleges; his name is mentioned in American encyclopedias and in books on the history of Russian literature; about the artistic world of Aksenov, reports are read at scientific conferences, candidate and doctoral dissertations are written, scientific monographic studies are published, articles are published in the most prestigious American literary journals.